Carbon nanotubes for hydrogen storage / Norhana Yahya … [et al.] - Yahya, Norhana; Hashim @ Ismail, Azhan; S.A., Halim; M., Hashim; R.S, Azis; N.M., Saiden; Z., Hari (Universiti Teknologi MARA Cawangan Pahang, 2002)
One major constrain in utilizing hydrogen, as an energy carrier is the absence of practical means to store them. Research on carbon nanotubes (CNTs) has been carried out tremendously due to the potential capacity to absorb hydrogen. This paper is an overview of what are CNTs, some experimental results on the hydrogen storage and our existing equipment to embark this work.